2016
DOI: 10.3892/ol.2016.4083
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell leukemia-1 is a molecular indicator for malignant transformation of oral lichen planus

Abstract: Abstract. Oral lichen planus (OLP), characterized by a chronic mucocutaneous inflammatory condition, is a common disease of the oral cavity. Retrospective and prospective epidemiological data suggest that OLP is considered to have malignant potential. However, it is unclear as to which types of molecules may cause malignant transformation of OLP. In the present study, the presence of myeloid cell leukemia-1 (Mcl-1) and B-cell lymphoma-2 (Bcl-2) was studied by western blot analysis in 11 OLP and three normal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Expression of MCL-1 was increased in OLP lesions and in the 2 tested cell lines, compared to that in the normal mucosa. The study highlighted the decrease of MCL-1 expression in cancer lines after treatment with sorafenib and mithramycin A, along with a decrease in cell replication, suggesting that the decline of MCL-1 expression could influence the process of malignant transformation [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Expression of MCL-1 was increased in OLP lesions and in the 2 tested cell lines, compared to that in the normal mucosa. The study highlighted the decrease of MCL-1 expression in cancer lines after treatment with sorafenib and mithramycin A, along with a decrease in cell replication, suggesting that the decline of MCL-1 expression could influence the process of malignant transformation [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various tissues, cells and saliva have TF activity [12,13]. Recently, Shin et al reported that OLP is considered to have malignant potential, and it is unclear regarding which types of molecules may cause malignant transformation of OLP [14]. Therefore, this study aimed to evaluate whether salivary oxidative stress-based TF level and activity changes could be a link between OLP and its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…OSCC cell lines exhibit significantly high expression of Mcl-1, which occurs through genetic amplification ( 21 , 46 ). As a commonly amplified and upregulated protein in OSCC malignant lesions, Mcl-1 promotes the development of cancer and reduces the survival of patients with cancer ( 21 , 47 ). As targeting Mcl-1 may be an important step in inducing programmed cell death, the use of natural compounds to attenuate Mcl-1 expression is considered a promising strategy for developing preventative and therapeutic regimens in OSCC ( 22 , 48 ).…”
Section: Discussionmentioning
confidence: 99%